External validation of the ProVent score for prognostication of 1-year mortality of critically ill patients with prolonged mechanical ventilation: a single-centre, retrospective observational study in Austria. Issue 9 (20th September 2022) - Dibiasi, Christoph; Kimberger, Oliver; Bologheanu, Razvan; Staudinger, Thomas; Heinz, Gottfried; Zauner, Christian; Sengölge, Gürkan; Schaden, Eva
Abstract : Objectives: In critically ill patients requiring mechanical ventilation for at least 21 days, 1-year mortality can be estimated using the ProVent score, calculated from four variables (age, platelet count, vasopressor use and renal replacement therapy). We aimed to externally validate discrimination and calibration of the ProVent score and, if necessary, to update its underlying regression model. Design: Retrospective, observational, single-centre study. Setting: 11 intensive care units at one tertiary academic hospital. Patients: 780 critically ill adult patients receiving invasive mechanical ventilation for at least 21 days. Primary outcome measure: 1-year mortality after intensive care unit discharge. Results: 380 patients (49%) had died after 1 year. One-year mortality for ProVent scores from 0 to 5 were: 15%, 27%, 57%, 66%, 72% and 76%. Area under the receiver operating characteristic curve of the ProVent probability model was 0.76 (95% CI 0.72 to 0.79), calibration intercept was −0.43 (95% CI −0.59 to −0.27) and calibration slope was 0.76 (95% CI 0.62 to 0.89). Model recalibration and extension by inclusion of three additional predictors (total bilirubin concentration, enteral nutrition and surgical status) improved model discrimination and calibration. Decision curve analysis demonstrated that the original ProVent model had negative net benefit, which was avoided with the extended ProVent model. Conclusions: The ProVent probability model had adequate discrimination but was miscalibrated in our patient cohort and, as such, could potentially be harmful. Use of the extended ProVent score developed by us could possibly alleviate this concern.